In Situ Techniques for Developing Robust Li–S Batteries. Issue 11 (1st August 2018) - Li, Ming; Amirzadeh, Zhila; De Marco, Roland; Tan, Xin Fu; Whittaker, Andrew; Huang, Xia; Wepf, Roger; Knibbe, Ruth
Abstract: Rechargeable lithium–sulfur batteries (LSBs) are of great interest in the field of energy storage due to their favorable operational characteristics, for example, high theoretical energy density and low cost. However, LSBs are limited by long‐term degradation, caused by the dissolution of intermediate lithium polysulfide phases. Further improvement of LSBs requires an in‐depth understanding of the underlying redox reactions and active‐material degradation mechanisms. Advanced characterization techniques, especially in situ/in operando characterization tools, are used and developed in the field of LSBs to probe the rate‐limiting performance and design characteristics of functional materials. Here, common in situ/in operando techniques are reviewed with regard to recent research significance and practical limitations, with the aim of providing a comprehensive treatise on in situ characterization technique selection for LSBs, thereby allowing their future development and improvement. Abstract : Lithium–sulfur batteries (LSBs) are of great interest in the field of energy storage due to their favorable operational characteristics, but they are limited by long‐term degradation. Further improvement of LSBs requires an in‐depth understanding of the underlying mechanisms via in situ characterization tools. The common in situ techniques are reviewed with regard to recent research significance and practical limitations.